I'm reading a book at the moment about logic gates and Boolean simplification. There is a part which I can't seem to follow.
I can easily work out that $A \vee (\neg A \wedge B) \equiv A \vee B$ using a truth table as it's easy to see.
However, I can't seem to turn $A \vee (\neg A \wedge B)$ into $A \vee B$ using steps such as distributive / absorption etc.
Can someone talk me through the steps that you would take to simplify this?
Asked By : user1480135
Answered By : Raphael
Note that
$\qquad A \lor (B \land C) \equiv (A \lor B) \land (A \lor C)$;
you can "multiply out". Add in
$\qquad (A \lor \lnot A) \land B \equiv B$
and you are done.
Best Answer from StackOverflow
Question Source : http://cs.stackexchange.com/questions/63769
0 comments:
Post a Comment
Let us know your responses and feedback